Polymerase chain reaction for detection of invasive Shigella flexneri in food. - Lampel, K A (1990)
The polymerase chain reaction (PCR) was used to amplify a 760-base-pair (bp) fragment with the 220-kbp invasive plasmids of enteroinvasive Escherichia coli, Shigella flexneri, Shigella dysenteriae, Shigella boydii, and Shigella sonnei as templates. This PCR product was easily detected by agarose gel electrophoresis. A 210-bp AccI-PstI fragment lying within the amplified region was used as a probe in Southern hybridization blots and showed that the PCR-generated product was derived from the invasive plasmid. The application of PCR as a rapid method to detect enteroinvasive bacteria in foods was tested by inoculating lettuce with 10(4) S. flexneri cells per g in shigella broth base. Plasmid DNA was isolated from cultures of inoculated and uninoculated lettuce in broth after 0, 4, and 24 h of incubation. With the PCR, the 760-bp fragment was generated only from lettuce inoculated with S. flexneri, as shown by gel electrophoresis and confirmed both by Southern blotting and by nucleotide sequencing of the amplified region. Because the isolation of plasmid DNA, the performance of PCR, and gel electrophoresis all can be completed in 6 to 7 h, invasive enteric bacteria can be detected in less than 1 day.